2004
DOI: 10.1089/acm.2004.10.861
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Complementary and Alternative Medicine in Eastern Turkey

Abstract: This study revealed that there is a high prevalence of use of alternative therapies by individuals living in eastern Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 29 publications
3
32
0
2
Order By: Relevance
“…For medication to have the desired result, it should be taken as prescribed (Tan et al, 2004). However, far too often people do not take their medication properly.…”
Section: Discussionmentioning
confidence: 99%
“…For medication to have the desired result, it should be taken as prescribed (Tan et al, 2004). However, far too often people do not take their medication properly.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey this rate is between 54.3% and 70% [9,10,15]. There are regional differences in terms of the prevalence and the method of CAM in the world.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with South Korean adults reported that 62% of adults had taken a dietary supplement [19]. Two studies in Turkey showed that herbs were the most frequently cited therapies [15,20]. Another study reported that herbal medicine (56.7%) and foods (78.5%) were used by the patients with COPD [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Turkey so far have focused on social use or on specific diseases like cancer or asthma. 13 Given the widespread public interest in CAM methods and their use, we were interested in hearing the opinions of physicians working in university hospitals on CAM. We found that the physicians in general were quite cautious about CAM while younger and female physicians were slightly more eager.…”
Section: Discussionmentioning
confidence: 99%